Contribution of Secondary Particles to Wintertime PM2.5 During 2015–2018 in a Major Urban Area of the Sichuan Basin, Southwest China. Issue 6 (17th June 2020) - Du, X. X.; Shi, G. M.; Zhao, T. L.; Yang, F. M.; Zheng, X. B.; Zhang, Y. J.; Tan, Q. W.
Abstract: A novel method, noted as approximate envelope method (AEM), was developed to estimate the secondary PM2.5 concentrations based on the air quality monitoring data. This approach made it possible to obtain the long‐term characteristics of the secondary PM2.5 using only conventional observations. The secondary PM2.5 concentrations and their variation characteristics under different PM2.5 pollution levels during wintertime of 2015 to 2018 in Chengdu, a major urban area of Sichuan Basin over Southwest China, were analyzed. The results showed that the secondary PM2.5 concentrations ranged from 52.3 to 122.8 μg·m −3 and accounted for 56.3%, 63.6%, and 67.4% of the total PM2.5 in slight, moderate, and heavy pollution status, respectively. Additionally, the concentrations of secondary PM2.5 increased year by year, while the concentrations of primary PM2.5 performed significant decreasing trends from 2015 to 2018. The diurnal variations of primary and secondary PM2.5 presented a significantly unimodal patterns but with maximum at morning and noon, respectively. Specific meteorological conditions such as high (low) relative humidity and temperature (wind speed and air pressure) aggravated the secondary particulate pollution in wintertime of Chengdu, reflecting an influence of regional climate change over the Sichuan Basin of Southwest China on the urban air pollution. Key Points: The PM2.5 /CO ratio is a valid tracer for estimating the concentration of primary particles Secondary particles dominated wintertime PM2.5 in urban area of Chengdu